ANALISIS KESIAPAN GURU KELAS DALAM IMPLEMENTASI PENILAIAN OTENTIK PADA KOMPETENSI RANAH SIKAP DI SD NEGERI KECAMATAN TEBING TINGGI KOTA - Juli Andriani; Deny Setiawan; Rahmad Husein (JURNAL TEMATIK, 2018)
This study aimed to obtain a factual description of teacher’s readiness in the implementation of authentic assessment for attitude domain in elementary schools Tebingtinggi. The problems of this study were the lack of socialization and training provided to the teacher, the teachers were still not optimal in the process of implementing the assessment was still considered very difficult. The method used in this research was descriptive qualitative research. The fourth grade teachers at 3 different elementary schools, SD Negeri 163080, SD Negeri 163084 and SD Swasta Inti Nusantara Tebing Tinggi. Data collection techniques used in this research were observation, interviews, and documentation. The data analysis from interviews, observation and documentation showed that the readiness of teachers authentic assessment for attitude domain implementation was still not ready.